Pengaruh Diaphragmatic Breathing dan Endurance Exercise Terhdap Peningkatan Kapasitas Kardiorespirasi Pada Pasien Hospital-Acquired Pneumonia - Azzahra, Alifia; Puspitarani, Annisya; Sativani, Zahra; Pahlawi, Riza (Jurnal Fisioterapi Terapan Indonesia, 2022)
The purpose of this case study is to determine the effect of diaphragmatic breathing and endurance exercise in hospital-acquired pneumonia (HAP) cases. HAP is a nosocomial pneumonia that occurs 48 hours or more after the patient is admitted to the hospital, without any signs of pulmonary infection at the time of initial treatment. The existence of clinical manifestations that appear, patients with HAP tend to avoid physical activity which can decrease the functional capacity of the respiratory system and have an impact on decreasing endurance. Diaphragmatic breathing exercise is thought to be able to help reduce shortness of breath, reduce the work of the accessory muscles of breathing, improve breathing frequency and also improve breathing patterns. Endurance training aims to increase the stimulation of the cardiorespiratory system response so that oxygen transportation becomes more efficient and the patient is able to carry out optimal activities. The method used in this case study is an evidence-based case report with a clinical question, "Does diaphragmatic breathing exercise and endurance exercise have a better effect on increasing endurance in hospital-acquired pneumonia?" To be able to answer this question, a case study was conducted by applying diaphragmatic exercise and endurance exercise, then to support the evidence from the results of the opener exercise, evidence was searched in 2 databases, namely Scopus and Science Direct. The keywords used were “diaphragmatic breathing exercise” OR “deep breathing exercise” AND “reduce dyspnea” and “endurance exercise” AND “cardiorespiratory endurance” AND “metabolic equivalents” with the inclusion criteria of full text articles and publications in 2015-2020. The search found 7 articles that met the inclusion criteria. Then the search stage was continued by reading the entire article and found 3 articles on Scopus and 1 article on Science Direct.